Assessing the Feasibility of a Digital Platform for Early Suicide Risk Screening among College Students - Lenny Aprilianty; Heni D. Windarwati; Lilik Supriati (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
College students’ mental health has become an increasingly prominent issue in recent years due to the rising prevalence of psychological problems such as stress, anxiety, depression, and suicidal ideation. Early detection efforts are essential to prevent the more serious consequences of these conditions. This study aims to analyze the use of digital platforms as an early screening tool for suicide risk among college students. A descriptive quantitative approach was employed, involving 225 students who participated in an online screening process. The instrument used in this study was the Beck Scale for Suicide Ideation, which was distributed through an online questionnaire using Google Forms. The results showed that the majority of respondents were in the low-risk category (200 respondents), while 23 respondents were classified as moderate risk and 2 respondents as high risk. These findings suggest that digital platforms can be utilized as an effective means of conducting early screening for college students’ mental health. The use of digital-based screening enables faster risk identification and allows researchers to reach a wider range of respondents, thereby supporting efforts to prevent mental health problems in higher education environments. Overall, this study highlights the value of integrating digital screening into university mental health systems and underscores the importance of further developing technology?supported prevention strategies in higher education settings. Contribution to Sustainable Development Goals (SDGs):SDG 3 : Good Health and Well?BeingSDG 4 : Quality EducationSDG 10 : Reduced InequalitiesSDG 16 : Peace, Justice, and Strong Institutions